Towards a common PPP framework for ASEAN - Abdul Rashid, Khairuddin (Routlegde, Taylor & Francis Group, 2018)
The countries of the Association of South East Asian Nations or ASEAN aspire to achieve regional economic integration by 2020 (ASEAN Economic Community or AEC). One of the most significant targets of the AEC is perhaps the establishment of a well-connected, highly competitive, and resilient ASEAN wherein people, goods, services, and capital are closer together. Infrastructure, therefore, is urgently needed. Among the constraints in establishing infrastructure is the difficulty of the public sectors of most member countries to provide adequate funding. Consequently, they entice their private sectors to assist through the provision of funds as well as expertise. As such, public-private cooperation via public-private partnerships, or PPP, is seen by ASEAN as among the most viable alternatives. This chapter examines PPP implementation in ASEAN member countries and assesses the prospect of having a common PPP framework for ASEAN. In conducting the assessment, the PPP implementation framework within the European Union (EU) is used as a benchmark. Outcomes of the examination include that a country-specific PPP implementation framework exists in each of the ASEAN member countries but that the framework differs from one country to another. In addition, ASEAN member countries are at different stages of PPP implementation maturity. In the context of the provision of infrastructure, the diverse PPP implementation frameworks may not be beneficial or could even act as among the impediments towards the realization of AEC 2020. The chapter concludes with views on the prospect of a common PPP implementation framework for ASEAN and highlights key areas considered appropriate to be harmonized.